Research progress on the therapeutic effects of polysaccharides on non-alcoholic fatty liver diseases - Hu, Yu-long; Ma, Qiaoli; Dong, Xiaoqiang; Kong, Yuanfang; Cai, Juntao; Li, Jieming; Dong, Chunhong (Frontiers in Nutrition, 2023)
Non-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease and is a leading cause of cirrhosis and hepatocellular carcinoma. Due to its complex pathophysiology, there is currently no approved therapy. Polysaccharide, a kind of natural product, possesses a wide range of pharmacological activities. Numerous preclinical studies have confirmed that polysaccharide could interfere with the occurrence and development of NAFLD at multiple interrelated levels, such as improvement of glucose and lipid metabolism, antioxidation, anti-inflammation, and regulation of liver-gut axis, thus showing great potential as novel anti-NAFLD drugs. In this paper, we reviewed the polysaccharides with anti-NAFLD effect in recent years, and also systematically analyzed their possible pharmacological mechanisms.